Influence of different filler weld wire chemistries on metallurgical and mechanical behavior of ultrahigh strength steel welded joints. (November 2019) - Sharma, Varun; Shahi, AS; Kumar, Subodh
Three different filler combinations comprising of ferritic, austenitic, and (ferritic + austenitic) were used to fabricate butt welded joints on 15 mm thick ultrahigh strength steel using hybrid arc welding processes. Owing to different weld metal compositions, a significant variation in metallurgical properties of these welds was observed, which consequently affected their mechanical properties in terms of tensile and impact toughness. Acicular ferrite with relatively soft zones formed in the ferritic weld metal imparted better impact toughness and ductility, whereas the joints welded using austenitic filler wire due to formation of hard martensitic structure showed high hardness across all their zones which resulted into higher tensile strength but poor ductility and impact toughness. SEM fractographs facilitated studying of shear lip formation and percentage shear area, and could be correlated with the ductility and impact toughness of the welded joints to a reasonable extent. Among all the welds, ferritic filler showed relatively less joint efficiency as well as ultimate tensile strength, but could be considered as a better choice over the austenitic as well their combination (ferritic + austenitic), as it performed better in terms of tensile ductility as well as impact toughness.